Effect of external flow on interior air quality - Law, Adrian Wing-Keung (Nanyang Technological University, 2008)
We investigate the re-entrainment of pollutants around a low-rise industrial building under opposing winds through experimental means in a wind tunnel. Two scaled models of an industrial building for electrowinning metal extraction were tested. The first model was a two-dimensional simplified segment of the building with a scale ratio of 1:40, while the second was a 1:100 three-dimensional model of the full building. Particle Image Velocimetry (PIV) was adopted to provide the planar velocity measurements that illustrated the flow distribution around the building. Flame Ionisation Detection (FID) with propane tracer gas was used to measure the concentration distribution.